Quantification by Quadrants of the Distortion Present in Conventional Panoramic Radiograph - Zúñiga,Janneth (Sociedad Chilena de Anatomía, 2017)
The panoramic radiograph constitutes the "gold standard" for any clinical evaluation in dentistry. It has been universally accepted that it has a global distortion of 25 % due to magnification. The present study was carried out to determine more precise percentages of distortion, and to find out whether the distortion was due to magnification or minimization. Thirty skulls with their mandibles were divided by two horizontal and four vertical planes in ten quadrants. Wires of different lengths were fixed in each of these quadrants. A panoramic radiograph was taken for each skull. The lengths of the wires measured in the images (distorted value) were compared to the actual lengths of the wires (real value). The concordance correlation coefficient was calculated. Due to high bone density, in the upper lateral quadrants (1 and 5) no measurements could be obtained. In the intermediate upper quadrants (2 and 4) and in the median lower quadrant (8), the horizontal measurements were minimized, while in the intermediate inferior quadrants (7 and 9) and in the lateral inferior quadrants (6 and 10), the horizontal measurements were magnified. In both the upper and the lower quadrants (2, 3, 4, 6, 7, 8, 9, 10) all the vertical measurements were magnified. The percentage of distortion in each quadrant for the horizontal and vertical measurements was reported. The percentage of distortion in a panoramic radiograph of the face varies from one region to another and can be due to either magnification or minimization.